2010
DOI: 10.4208/cicp.2009.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Flow Simulation via a Boundary Condition-Enforced Immersed Boundary-Lattice Boltzmann Scheme

Abstract: Abstract.A boundary condition-enforced immersed boundary-lattice Boltzmann method (IB-LBM) for the simulation of particulate flows is presented in this paper. In general, the immersed boundary method (IBM) utilizes a discrete set of force density to represent the effect of boundary. In the conventional IB-LBM, such force density is pre-determined, which cannot guarantee exact satisfaction of non-slip boundary condition. In this study, the force density is transferred to the unknown velocity correction which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…The results showed that, unlike other simulating methods, such as the direct numerical simulation [10] , the finite element method using moving unstructured grids [11] , and the distributed Lagrange multiplier/fictitious domain method [12] , the lattice Boltzmann method was simple, had a more close relationship with the micro scale physics, and its computation cost scaled linearly with the number of the particles [13] . The boundary treatment method is critical in the simulation study of the particulate flow, there are also some improved boundary treatment methods, such as the immersed boundary method [8,[14][15] , which are more accurate for the calculation of the particle fluid interaction. In general, the lattice Boltzmann method is a very promising method for the simulations of particulate flows.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, unlike other simulating methods, such as the direct numerical simulation [10] , the finite element method using moving unstructured grids [11] , and the distributed Lagrange multiplier/fictitious domain method [12] , the lattice Boltzmann method was simple, had a more close relationship with the micro scale physics, and its computation cost scaled linearly with the number of the particles [13] . The boundary treatment method is critical in the simulation study of the particulate flow, there are also some improved boundary treatment methods, such as the immersed boundary method [8,[14][15] , which are more accurate for the calculation of the particle fluid interaction. In general, the lattice Boltzmann method is a very promising method for the simulations of particulate flows.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Shu [41] developed a boundary condition enforced IB-LBM. In another investigation, they [36] introduced a new IB-LBM to simulate the migration of a neutrally buoyant particle in the Newtonian flow.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study we modify the IB-LBM presented by Wu and Shu [36] for the simulation non-Newtonian fluids around immersed boundaries and a new hybrid finite difference-immersed boundary-lattice Boltzmann method (FD-IB-LBM) has been used to study the muco-ciliary transport problem. In this method the main part of the momentum equation (which contains the nonlinear advection term) has been solved by the lattice Boltzmann method (LBM) which is characterized by simple computation, parallel process and easy implementation of boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to accurately compute the hydrodynamic force acting on the boundaries of particles. In terms of accuracy in resolving ow eld, it was shown that the boundary condition-enforced IB-LBM provides a simple and accurate way to compute lift and drag (vertical and horizontal) forces exerted on the immersed object [15].…”
Section: Introductionmentioning
confidence: 99%